Application Of Gulijat Techniques On Textile Products Of The MGMP Art And Culture SMK Of Gresik - Ratyaningrum, Fera; Marsudi, Marsudi; Camelia, Ika Anggun; Sampurno, Muchammad Bayu Tejo (Proceeding of International Joint Conference on UNESA, 2024)
Gulijat cloth is the name for cloth decorated using a combination of folding and knitting. Gulijat itself is an abbreviation of roll-fold-jump-tie. The motifs produced from this technique are different from jumput or shibori fabrics. This service activity aims to increase knowledge and skills as a provision to enable students to create fine arts. Considering the existing level of education, of course more than one knowledge and skill is needed. Knowledge and skills in the field of fine arts are still minimal for most members of the Gresik Regency Vocational School Arts and Culture MGMP because their educational background is not in the field of arts, including fine arts. The research method used is qualitative research presented descriptively. Data collection was obtained from documentation studies, questionnaires and direct observation. The research subject was the Gresik High School-Vocational School Arts and Culture MGMP. To validate the implementation data with triangulation. As a result of the training, partners have been able to practice Gulijat techniques according to the correct procedures and the products created show clear motifs. After attending this training, it is hoped that the MGMP Arts and Culture participants at the Gresik Regency Vocational School will be able to teach it to students at their respective schools.